2010
DOI: 10.1016/j.cma.2010.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Maximum-entropy meshfree method for compressible and near-incompressible elasticity

Abstract: Numerical integration errors and volumetric locking in the near-incompressible limit are two outstanding issues in Galerkin-based meshfree computations. In this paper, we present a modified Gaussian integration scheme on background cells for meshfree methods that alleviates errors in numerical integration and ensures patch test satisfaction to machine precision. Secondly, a lockingfree small-strain elasticity formulation for meshfree methods is proposed, which draws on developments in assumed strain methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 67 publications
0
63
0
Order By: Relevance
“…In the max-ent framework a stable formulation where max-ent basis functions are used to approximate the displacements and piece-wise linear FE shape functions are used for the pressure was introduced in [56] for compressible and near-incompressible elasticity. In order to ensure stability the displacement approximation is enhanced with an extra node in the interior of each integration triangle, resembling the MINI finite elements [57].…”
Section: Introductionmentioning
confidence: 99%
“…In the max-ent framework a stable formulation where max-ent basis functions are used to approximate the displacements and piece-wise linear FE shape functions are used for the pressure was introduced in [56] for compressible and near-incompressible elasticity. In order to ensure stability the displacement approximation is enhanced with an extra node in the interior of each integration triangle, resembling the MINI finite elements [57].…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [1], we have shown that the use of (15) whose support is the intersection of the support of φ a and φ b and as such can differ appreciably from the union of the cells used in the numerical integration. As a consequence, significant numerical errors can be expected from the numerical integration using (15) or (16).…”
Section: Discrete Weak Formmentioning
confidence: 99%
“…and performing row-sum in the pressure term leads to Now, solving for p a in (13), the following volume-averaged nodal pressure is obtained [1]:…”
Section: Discrete Weak Formmentioning
confidence: 99%
See 2 more Smart Citations